Window to the Womb: Amniotic Fluid and Postnatal Outcomes - Whittington JR; Ghahremani T; Friski A; Hamilton A; Magann EF (Dove Medical Press, 2023)
Julie R Whittington,1 Taylor Ghahremani,2 Andrew Friski,1 Andrew Hamilton,1 Everett F Magann1 1Women's Health Department, Naval Medical Readiness and Training Center Portsmouth, Portsmouth, VA, USA; 2Department of OB/GYN, University of Arkansas for Medical Sciences, Little Rock, AR, USACorrespondence: Julie R Whittington, Women's Health Department, Naval Readiness and Training Command Portsmouth, 620 John Paul Jones Circle, Portsmouth, VA, 23321, USA, Tel +1-979-848-9665, Email Julie.whittington09@gmail.comAbstract: Amniotic fluid volumes are tightly regulated, and amniotic fluid derangement can indicate maternal complications or fetal abnormalities. Ultrasound estimate of amniotic fluid provides a tool to evaluate the maternal-fetal-placental interface in real-time. Oligohydramnios and polyhydramnios are associated with adverse maternal and neonatal outcomes. Oligohydramnios is associated with adverse maternal and neonatal outcomes including cesarean delivery, operative vaginal delivery, induction of labor, postpartum hemorrhage, small for gestational age neonate, intrauterine demise, neonatal death, NICU admission, and APGAR less than 7 at. 5 minutes of life Polyhydramnios is associated with adverse outcomes including cesarean delivery, induction of labor, placental abruption, shoulder dystocia, cord prolapse, postpartum hemorrhage, intrauterine fetal demise, NICU admission, neonatal death, APGAR less than 7 at 5 minutes of life, large for gestational age neonate, and respiratory distress syndrome. Therefore, Amniotic fluid should be evaluated when maternal or fetal well-being is in question.Keywords: oligohydramnios, polyhydramnios, perinatal outcomes, single deepest pocket